Acomparative Evaluation of Anaesthetic Effectiveness Of 4 % Articaine ,0.5 % Bupivacaine And 2 % Lignocaine in General Tooth Extraction - Shinde, Rajlaxmi (Journal of Neonatal Surgery, 2025)
Background Nowadays safe and efficient pain control is essential for today’s dental practice. That randomized controlled study was conducted to evaluate the effectiveness of 4 % articaine ,0.5 % bupivacaine and 2 % lidocaine for removal of tooth. The local anaesthetic solutions in tooth removal depends on the following points: latency, anaesthetic effectiveness and duration of anaesthetic effect. Objectives The objectives of an study are to evaluate the analysis of anesthetic solutions of 4% Articaine, 0.5 % Bupivacaine and 2%Lignoacaine using the Visual analogue scale ( VAS SCALE ). Study design: This randomized control study was performed in the oral surgery department from 1/8/2024 to 1/11/2024 The study between 150 patients of both sexes who come to oral surgery department for removal of tooth in the age between 20-60 years. Materials and methods The study involved 150 patients of both sexes, aged 20-60 years, who visited the oral surgery department for tooth extraction. Participants were randomly assigned into three groups of 50 patients each. The anesthetic solutions used for the extraction were as follows: Group A: 0.5% bupivacaine with 1:200,000 epinephrine Group B: 4% articaine with 1:100,000 epinephrine Group C: 2% lignocaine with 1:100,000 epinephrine The comparative analysis was conducted to evaluate the onset of anesthesia, duration of pain relief, and overall effectiveness of the different anesthetics used during the extraction process . Results The results indicated that 4% articaine was superior to both bupivacaine and lignocaine in terms of efficacy for tooth extraction procedures. Articaine provided quicker onset and longer-lasting anesthesia, making it the preferred choice for routine extractions.